Minha pátria é minha língua: língua e identidade nacional - Vilela-Ardenghi, Ana Carolina Nunes da Cunha (2007)
At first, the aim of this research was to analyse discourses on the national linguistic identity that appeared in the news pieces published by Folha de S.Paulo, between 2001 and 2005. The initial selection of the pieces allowed us to notice, however, that the debate about the language was part of a much bigger context: the discussions about the legitimation of a national identity. From that, we could formulate the central hypothesis of this research, which is, the debates about national identity is based on the linguistic factor. In other words, the language is the element that supports the discussions on national identity. These debates, in turn, are developed, in Folha de S.Paulo, on two different thematic axles . In the first one, the Portuguese language is confronted with English, and from that confrontation a severe controversy arises regarding the foreign expressions coming from English and used in Portuguese. The news pieces from this axle indicated to us that the discussions were not about the legitimation of the linguistic identity, as one may assume at first, but about the national identity itself. The second axle, on the other hand, confronted the Brazilian variety of Portuguese language with the other worldwide varieties, and, in this scene, the polemic viewed as a violent controversy did not take place and the Brazilian variety, and, consequently, Brazil, was given a leadership role among the other Portuguese-speaking countries, including Portugal, the former metropolis. To proceed the analysis of the 40 selected pieces of news of our corpus, we used the theoretical formulations of the French school of Discourse Analysis, especially some concepts developed by Dominique Maingueneau inside the proposition of a global semantics.